PENGARUH RASIO UTANG TERHADAP EKUITAS DAN RASIO LANCAR TERHADAP PENGEMBALIAN ASET PT. SEPATU BATA TBK - M. Kausar Maulana; Annisa Salsa Sabrina (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research aims to analyze the influence of debt to equity ratio and current ratio on return on assets in PT. Bata Shoes Tbk. The research method used is a quantitative analysis method. The sample used of the company PT. Shoes Bata Tbk.This research uses annual financial report data with 4 quarters per year. The type of data is secondary which is taken from the Indonesian Stock Exchange. The data analysis technique uses multiple linear regression analysis. The results of this research indicate that the debt to equity ratio and current ratio simultaneously have a significant influence on return on assets. Debt to equity ratio partially has a positive and significant influence on return on assets. Current ratio partially has a positive and significant influence on return on assets.